Pengaruh Strategi Pembelajaran dan Kemampuan Berpikir Kritis Terhadap Hasil Belajar Sejarah Siswa SMA Negeri 72 Jakarta - Veronika Horohiung (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2017)
The aim of this research is to find The influence of Instructional Strategy and Critical Thinking to History Learning Outcomes in SMA Negeri 72 Jakarta. The type of this research is used experiment design treatment method. The Instrument that used to know the learning outcomes is Multiple Choice, and the instrument that used to know the result of Critical Thinking is Quisioner. The result of this research refer to: (1) to history learning outcomes that was giving PBL Instructional Strategy is higher than students who was giving Direct Instructional. (2) there is influenace interaction between Instructional Strategy and Critical thinking. (3) history learning outcomes that was giving PBL Instructional Strategy and has Critical Thinking is higher than student who was giving Direct Instructional Strategy and has high Critical Thinking. (4) history learning outcomes that was giving PBL Instructional Strategy and the Critical Thinking is lower than student who was giving Direct Instructional Strategy and has low Critical Thinking.